Clinicopathological analysis of IgA nephropathy combined with hyperuricemia - CAI Wei-cheng; HAN Shu-lian; GUO Xiao-dan; LING Yi-sheng; LIU Jun-lan; GUAN Tian-jun (Linchuang shenzangbing zazhi)
Objective To investigate the clinicopathological characteristics of IgA nephropathy combined with hyperuricemia in order to reveal the clinical significance of IgA nephropathy associated with hyperuricemia.Methods We retrospectively reviewed the clinical data of 270 patients with IgA nephropathy diagnosed by renal biopsy from June 2006 to December 2012.The patients were divided into the two groups:IgA nephropathy patients with or without hyperuricemia.The sex,age,systolic blood pressure,24-h urine protein,serum uric acid,and serum creatinine were measured.All patients underwent renal pathological examination and Lee’s classification.A comparative analysis of clinical manifestations and renal pathological injuries was performed between the two groups,and the pathological parameters of patients with normal renal function were further analyzed.Results The prevalence of hyperuricemia in patients with IgA nephropathy was 25.19%.The systolic blood pressure,24-h urine protein and serum creatinine level were higher in the hyperuricemia group than in the normal group.The renal pathological changes in the hyperuricemia group were more severe than those in the normal uric acid group.The proportion of renal tubular interstitial lesions and renal artery lesions in the hyperuricemia group was higher than in the normal renal function group.The proportion of renal artery stenosis and renal tubular interstitial chronic lesions in the patients with hyperuricemia group was higher than in normal serum uric acid group.Conclusions The clinical manifestations and renal pathological changes of patients with IgA nephropathy combined with hyperuricemia are more serious than those with normal serum uric acid level,in particular,the effects of renal tubular interstitial lesions and renal vascular lesions were more obvious,and the clinical prognosis is not good.Timely and effective treatments are needed.